Studi Peneriman Konsumen Terhadap Stick Todak (Xiphias Gladius) dengan Penambahan Daging dan Tulang yang Berbeda - Lucia Dewi Indrayani Manurung; Ahyani Ridhayani Lubis; Sutriana Sutriana (KOLONI, 2023)
Swordfish is a type of marine fish with an upper jaw and an elongated snout shaped like a flat and strong sword measuring almost one-third the length of the fish's body. The long and strong snout is used to kill its prey. This fish is widely found in the Pacific Ocean, Atlantic Ocean and Indian Ocean. Swordfish are included in the group of fish that swim at high speed. This fish can reach speeds of 96 km / h. Swordfish is a form that is less attractive to the public. The treatments used in making swordfish sticks were A1 (200 grams 0% bone), A2 (125 g meat and 75 g bone), A3 (100 g meat and 100 g bone), A4 (75 g meat and 125 g bone). . This research uses hedonic test and proximate test. The parameters tested were hedonic (appearance, aroma/smell, taste and texture), with a proximate test (moisture, ash, fat, protein and carbohydrate content). The results showed that the manufacture of swordfish sticks with the addition of meat and bones with different concentrations resulted in the appearance, aroma/smell, taste and texture favored by consumers. A1 treatment on appearance got a value (7.56), A1 treatment on aroma/smell got a value (7.18), A1 treatment on taste got a value (7.66) and the level of preference for A1 treatment on texture got a value (7.40 ). The proximate/chemical test results obtained water 2.36, ash content 3.38, protein content 10.65, carbohydrate content 22.48 and fat 37.31.